Strategi Pengelolaan Bandar Udara Sultan Muhammad Salahuddin Melalui Kompetensi dan Disiplin Karyawan Berkontribusi pada Level Of Service - Hasanah, Khaimatul; Rafi, Salahudin; Majid, Suharto Abdul; Agusinta, Lira; Kurniawan, Jermanto Setia; Kania, Dinar Dewi (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2023)
Based on the observation in Sultan Muhammad Salahuddin Bima Airport, West Nusa Tenggara, several problems were found; the check-in counters were often disrupted or damaged, damage luggage could occur due to porters, incompetent employees in some fields, and indiscipline employees as the act of not paying attention to the company’s regulation. This study aims to determine the strategy for managing employees’ competencies and discipline at work that could contribute to the level of service at this airport and to which extent the role of employees’ competencies and discipline could increase the level of service. This study used SWOT analysis and interview as the research method. The results of the study show that the position of the airport is in a strong competitive position. Sultan Muhammad Salahuddin Bima airport should continue its effort to improve its employees’ capabilities, discipline at work and to provide the supporting facilities of all aspects including increasing airport capacity and improving the human resources quality of airport management.